Mecanismos fotossintéticos e osmoproteção induzidos por silício em plantas de mamoeiro sob défcit hídrico - Silva Júnior, Eugênio Gonçalves da (2018)
Brazil is the second largest producer of papaya (Carica papaya L.) with over 1.6 million tons per year, with the Northeast region accounting for 64% of production. However, one of the main limiting factors of the productivity of this crop in this region is the irregularity of rainfall. Thus, it is fundamental to enable alternative means of minimizing damages or inducing tolerance to water deficit by means of stress attenuating compounds such as silicon (Si). In this context, the present study proposed to evaluate the action of Si on the photosynthetic and osmotic mechanisms in papaya cultivated under conditions of water deficit. The experiment was conducted in tubes in greenhouse, using seeds of Hawai cultivar. Were tested three concentrations of Si (0.0, 1.5 and 2.5 mL L^-1) and four irrigation slides (20; 40, 60 and 80% of the field capacity). A completely randomized design was used, combined in the 3x4 factorial scheme with four replications and three useful plants per plot, totaling 144 experimental units. The silicon was applied via foliar and to evaluate the effects of the treatments were considered growth parameters, biochemical and physiological. The results were submitted to analysis of variance by the F test, up to 5%, and the test of comparison of means (Tukey, P <0.05) was applied, when there was interaction for the Si within the irrigation slides. It was observed that the water deficit caused a reduction in t he growth and physiological variables. However, the application of Si benefited the root growth, the height of the seedlings and the number of leaves, improving the photosynthetic efficiency due to the increase in the chlorophyll content and favored gain in the rates of liquid photosynthesis, transpiration, stomatal conductance and internal CO2 concentration. The application of 1.5 mL L^-1 of Si increased the levels of nitrogen compounds, such as total soluble proteins, total free amino acids, proline and glycine betaine, as well as the content of starch and total soluble sugars. suggesting that papaya seedlings can be grown with 60% of field capacity when treated with 1.5 mL L^-1 of Si.